2024
DOI: 10.3390/ani14020319
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Improved the Quality of Hu Ram Semen by Increasing the Antioxidant Capacity and Mitochondrial Potential and Mitigating Free Radicals-Induced Oxidative Damage

Tariq Sohail,
Liuming Zhang,
Xuyang Wang
et al.

Abstract: The objective of this research was to investigate the effect of astaxanthin supplementations of semen extender on the quality of Hu ram semen after up to five days of preservation at 4 °C. Semen samples were collected from five healthy Hu rams using an artificial vagina during breeding season (April to August 2023) and diluted with a basic extender supplemented with control (0), 1 µM, 2 µM, 3.5 µM, or 4.5 µM of AXT. Overall, 170 semen ejaculate samples (34 repetitions) from five healthy Hu rams were used in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Studies indicate that coenzyme Q10 supplementation improves mitochondrial function in sperm cells, leading to increased energy production and enhanced sperm movement, which are essential for successful fertilization [68]. Sohail T. et al (2024) demonstrated that supplementation of an optimal concentration of astaxanthin (AXT) at 3.5 µM in Hu ram semen preservation markedly enhances its kinematic properties, longevity, plasma membrane integrity, acrosome integrity, total antioxidant content, and mitochondrial membrane potential. Conversely, the inclusion of AXT at 3.5 µM significantly diminishes ROS and MDA concentrations in spermatozoa, thereby extending their longevity and ultimately enhancing their fertilization potential [69,70].…”
Section: The Current Status Of Non-enzymatic Antioxidant Utilization ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that coenzyme Q10 supplementation improves mitochondrial function in sperm cells, leading to increased energy production and enhanced sperm movement, which are essential for successful fertilization [68]. Sohail T. et al (2024) demonstrated that supplementation of an optimal concentration of astaxanthin (AXT) at 3.5 µM in Hu ram semen preservation markedly enhances its kinematic properties, longevity, plasma membrane integrity, acrosome integrity, total antioxidant content, and mitochondrial membrane potential. Conversely, the inclusion of AXT at 3.5 µM significantly diminishes ROS and MDA concentrations in spermatozoa, thereby extending their longevity and ultimately enhancing their fertilization potential [69,70].…”
Section: The Current Status Of Non-enzymatic Antioxidant Utilization ...mentioning
confidence: 99%
“…Sohail T. et al (2024) demonstrated that supplementation of an optimal concentration of astaxanthin (AXT) at 3.5 µM in Hu ram semen preservation markedly enhances its kinematic properties, longevity, plasma membrane integrity, acrosome integrity, total antioxidant content, and mitochondrial membrane potential. Conversely, the inclusion of AXT at 3.5 µM significantly diminishes ROS and MDA concentrations in spermatozoa, thereby extending their longevity and ultimately enhancing their fertilization potential [69,70]. AXT (C40H52O4) is a red carotenoid pigment sourced from the alga hematococcus pulvalis, renowned for its antioxidant, anticancer, anti-diabetic, and anti-inflammatory properties.…”
Section: The Current Status Of Non-enzymatic Antioxidant Utilization ...mentioning
confidence: 99%